“Widely Disseminated Violence”: Studying Variants of the Violence Represented or Described in the Evidence of the Ancient Near East. - Dolce, Rita (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2026)
Based on the research currently underway on violence, depicted or described, some variants are identified aside from officially displayed and heroic-epic violence. This violence, which I define as “widely disseminated violence”, is accomplished in different ways, indirect or subliminal, manifest or identifiable in the visual evidence, and also perceptible in the written sources.